Preimplantation genetic screening: does it help or hinder IVF treatment and what is the role of the embryo? - Ly, Kim Dao (Springer US, 2011)
Despite an ongoing debate over its efficacy, preimplantation genetic screening (PGS) is increasingly being used to detect numerical chromosomal abnormalities in embryos to improve implantation rates after IVF. The main indications for the use of PGS in IVF treatments include advanced maternal age, repeated implantation failure, and recurrent pregnancy loss. The success of PGS is highly dependent on technical competence, embryo culture quality, and the presence of mosaicism in preimplantation embryos. Today, cleavage stage biopsy is the most commonly used method for screening preimplantation embryos for aneuploidy. However, blastocyst biopsy is rapidly becoming the more preferred method due to a decreased likelihood of mosaicism and an increase in the amount of DNA available for testing. Instead of using 9 to 12 chromosome FISH, a 24 chromosome detection by aCGH or SNP microarray will be used. Thus, it is advised that before attempting to perform PGS and expecting any benefit, extended embryo culture towards day 5/6 should be established and proven and the clinical staff should demonstrate competence with routine competency assessments. A properly designed randomized control trial is needed to test the potential benefits of these new developments.